Isolation and Characterization of Antibacterial Actinomycetes from Soil Samples of Kalapatthar, Mount Everest Region - Gurung, Tara Devi; Sherpa, Chringma; Agrawal, Vishwanath Prasad; Lekhak, Binod (Nepal Journal of Science and Technology, 2010)
Seventy-nine Actinomycetes were isolated from soils of Kalapatthar (5545m), Mount Everest region. Twenty seven (34.18%) of the isolates showed an antibacterial activity against at least one test-bacteria among two Gram positive and nine Gram negative bacteria in primary screening by perpendicular streak method. Thirteen (48.15%) showed antibacterial activity in secondary screening. The result showed that three of the isolates, K.6.3, K.14.2, and K.58.5 were highly active with an inhibition zone e"20mm and broad spectrum antibacterial activity including two methicillin resistant Staphylococcus aureus (MRSA) strains. Minimum inhibitory concentration (MIC) of antibacterial metabolites of the isolate K.6.3 was 1mg/ml, and that of isolates K.14.2 and K.58.5 was 2mg/ml. Two spots were detected on thin layer chromatography plate from each of the metabolites which was completely different from the spot produced by vancomycin. The active isolates from primary screening were heterogeneous in their overall macroscopic, biochemical, and physiological characteristics through unweighted pair group method using average (UPGMA) cluster analysis. Delineation of the three active isolates showing potent broad spectrum antibacterial activity revealed that they belonged to distinct taxonomic groups. Key words: Antibacterial activity; Minimum inhibitory concentration; Thin layer chromatography DOI: 10.3126/njst.v10i0.2957 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 173-182